PENGARUH STRATEGI PEMBELAJARAN PEMECAHAN MASALAH BERORIENTASI MASALAH MATEMATIKA TERBUKA TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KETERAMPILAN METALOGNITIF PESERTA DIDIK KELAS XII SMA N 7 DENPASAR - Sukendra, I Komang; Sumandya, I Wayan (Widyadari: Jurnal Pendidikan, 2019)
This study aims to investigate the effect of the application of problem solving strategies oriented to open mathematical problems towards the achievement of learning mathematics, by paying attention to the factors of students' metacognitive skills. The research design used in this study was a 2 x 2 factorial research design, with a simple random sampling technique. This research is a quasi-experimental study. The population in this study were all students of class XII MIPA Public High School 7 Denpasar academic year 2018/2019 which consisted of 9 classes with a total of 324 people. With samples of class XII MIPA 2, XII MIPA 4, XII MIPA 5, and XII MIPA 8. Tests were carried out by t-test, F test, Tukey test through Anava Two-way statistical method.         From the results of data analysis, it was found that, (1) there was an influence of learning strategies on open mathematical problem-solving problem solving on students' mathematics learning achievement. (2) there is the influence of learning strategies on problem solving oriented open mathematical problems on mathematics learning achievement in students with high metacognitive skills. (3) there is the influence of learning strategies on problem solving oriented to open mathematical problems on mathematics learning achievement in students with low metacognitive skills. (4) there is no interaction between learning strategies and metacognitive skills on mathematics learning achievement of students.